PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN KEMANDIRIAN DAN HASIL BELAJAR PADA MATAKULIAH GEOMETRI DATAR DAN RUANG - I Dewa Putu Juwana; I Komang Sukendra; I Made Surat (Widyadari, 2024)
Independent learning is an activity that students carry out without depending on the help of other people, both friends and lecturers, in achieving learning goals, namely mastering material or knowledge well with their own awareness and students can apply their knowledge in solving problems in everyday life. However, there are still students who experience difficulties in independent learning. The purpose of this research is (1) to determine student learning independence in flat and spatial geometry courses through the application of problem solving learning models in mathematics education study programs. (2) to determine student learning outcomes in flat and spatial geometry courses through the application of problem solving learning models in mathematics education study programs. This type of research is classroom action research. The research subjects were students in the fourth semester of the mathematics education study program for the 2023/2024 academic year, PGRI Mahadewa University, Indonesia. The object of this research is student independence and learning outcomes after implementing the problem solving learning model. This research uses two cycles and each cycle consists of planning, action implementation, observation and reflection stages. The method used in this research is descriptive statistics. The results of the research show that the application of the problem solving learning model can increase learning independence and learning outcomes for students in the fourth semester of the mathematics education study program for the 2023/2024 academic year in the flat and space geometry courses at PGRI Mahadewa Indonesia University.